Clinical Significance of Serum Zinc Levels in Cerebral Ischemia - Archit Bhatt; Muhammad U. Farooq; Sailaja Enduri; Clement Pillainayagam; Bharath Naravetla; Anmar Razak; Adnan Safdar; Syed Hussain; Mounzer Kassab; Arshad Majid (Stroke Research and Treatment)
Background. Zinc mediates several vital physiological, enzymatic and cellular functions. The association between serum zinc and stroke outcome has not been previously evaluated. Methods. This single center retrospective study was conducted on consecutive stroke (𝑛=158) and TIA (𝑛=74) patients. We sought to determine whether serum zinc concentrations in patients with acute ischemic strokes were associated with stroke severity and poor functional status at discharge, respectively. Results. Overall, out of the 224 patients analyzed (mean age 67 years), 35.7% patients had low zinc levels (65 mcg/dL). Patients with stroke (𝑛=152) were more likely to have low zinc levels (OR=2.62, CI 1.92-3.57, 𝑃<.003) compared to patients with TIA (𝑛=72). For patients with stroke (𝑛=152), multivariate analysis showed that low serum zinc levels (OR 2.82, CI 1.35-5.91, 𝑃=.035) and strokes with admission severe strokes (NIHSS>8) (OR 2.68, CI 1.1-6.5, 𝑃=.03) were independently associated with poor functional status (MRS>3) at discharge from the hospital. Conclusion. Low serum zinc concentrations are associated with more severe strokes on admission and poor functional status at discharge.